Semantics Question Analysis Model for Question Answering System - Syarilla Iryani, Ahmad Saany; Mohd Nordin, Abdul Rahman; Ali, Mamat (Hikari Ltd., 2015)
Question Answering (QA) system takes Natural Language (NL) questions and output the exact answer extracted from Knowledge Base (KB). Handling NL question requires semantic analysis and interpretation to obtain the potential relevant answers from the KB. Providing users with the most relevant answers to their questions is an issue. Many answers returned are not relevant to the questions. The purpose of this paper is to present a semantic question analysis model for question answering system that correctly interpret the user’s question in order to yield correct answers. The Semantic Question Analysis Model exploits the approach of User Modelling and Relevance Feedback. To measure the ability of Semantic Question Analysis Model in analysing and translating user NL question, the model is implemented in an ontology-based question answering system (known as QAUF). Comparison of the results is done to determine the success of the proposed model with the existing QA systems, AquaLog and FREyA. The Semantic Question Analysis Model in QAUF shows a relatively increased in the QAUF F-measure. The finding of this study demonstrates that QAUF has a good precision percentage in returning relevant answers for each NL question.